Penentuan tahap kakisan tetulang keluli menggunakan kaedah pengecilan amplitud - Roszilah Hamid,; Khairul Anuar Mohd Nayan,; Kamarudin Mohd Yusof,; Wan Marzuliani Wan Mohd, (2009)
This study is to determine whether the amplitude attenuation method can be used to measure the corrosion rate of rebars without having to hack the sructure nor it need not to be in saturated form. A pressure wave is generated by dropping a small steel ball onto the concrete surface. This wave will propagate through the concrete and will be reflected by defects and the opposite surface of the concrete. The wave in the form of amplitude verses frequency is recorded. The frequency reflected by the rebar, fst, can be determined based on CP, the wave velocity in concrete, and the thickness of the concrete cover. Concrete prisms (300 × 150 × 150 mm3) of Grade 15 and 20, embedded with 20 mm diameter of rebar were immersed in 120g/l NaCl concentration for 42 days (G15N and G20N). Other samples were left immersed for 20 days and the corrosion process is accelerated by connecting the rebars to a direct current supply (G15E and G20E). Results show that the amplitud at fst for G15N reduces 21% from the 20th day of immersion to the 42nd day and 24% for G20N. For the samples that had undergone accelerated corrosion process (G15E), the fst amplitude reduction from day 14th of immersion to day 20th is 15% and 18% for G20E. The percentage reductions of electrical potential in the half-cell test are 52%, 50%, 28% and 16% during the same time duration. It can be seen that the amplitude attenuation measurement can determine the corrosion activity of the steel rebars. The overall reductions of amplitude are 46% (G15N), 43% (G20N), 54% (G15E) and 52%(G20E) respectively.